PENGARUH KEMAMPUAN KERJA TERHADAP KINERJA PEGAWAI DI PT. BPR MITRA TELAGASARI UTAMA KARAWANG - Feriandy Feriandy; Faras Zulina Ayunani; Zulkifli Rangkuti; Bambang Ermansyah Saragih; Aas Narsiah (Sekolah Tinggi Manajemen IMMI, 2022)
In this study there are two variables, namely Variable X (Work Ability) and Variable Y (Performance). This research was conducted to determine the workability of PT. BPR Mitra Telagasari Utama Karawang, Employee Performance at PT. BPR Mitra Telagasari Utama Karawang.The method used in this study is descriptive analysis method to discuss the formulation of the problem how the work ability of employees at PT. BPR Mitra Telagasari Utama Karawang and Work Discipline at PT. BPR Mitra Telagasari Utama Karawang, and verification analysis to discuss the formulation of the problem how much influence Workability has on Employee Performance at PT. BPR Mitra Telagasari Utama Karawang. The data used are primary and secondary data collected through observation, interviews, questionnaires (questionnaires) and literature. The hypothesis of this research is that there is an effect of Work Ability on Employee Performance at PT. BPR Mitra Telagasari Utama Karawang. To measure the magnitude of the effect of these variables, Simple Linear Regression and Correlation Coefficients and Coefficients of Determination were used with the help of the IBM SPSS application program.Based on the results of data analysis using statistical methods, namely Simple Linear Regression, the Coefficient of Determination (KD) of 3.41. Based on these results, it can be concluded that work ability has an effect on employee performance at PT. BPR Mitra Telagasari Utama Karawang.Keywords: Workability and Performance